The Impact of Capital Reduction on Share Prices: An Event Study of Companies Listed on the Saudi Stock Exchange (Tadawul) (Global Journal of Sciences, 2025)
This research evaluates the impact that capital reduction announcements have on the  stock prices of firms that are listed on the Saudi Stock Exchange (Tadawul) between  2020 and 2024. Specifically, the study will focus on the period between 2020 and 2024.  This research makes use of the event study methodology in order to assess the  effectiveness of the market as well as the actions of investors in response to business  events. In order to achieve this task, it is necessary to evaluate the course of market  responses and the timing of those reactions. To be more specific, the objective of this  study is to analyze whether or not the reduction in capital serves as an early warning  sign of financial difficulties, or whether or not it is a deliberate process of financial  restructuring with the idea of boosting the organization's worth over the long run.  According to the findings of empirical research, announcements of a decrease in capital  at the time of the event do not evoke a market reaction that is statistically significant in  a negative direction. After an initial period of investor concern, the data suggests that  there was a relatively favorable cumulative impact. This is in contrast to the previous  statement. The fact that this is the case shows that market participants may see these  declarations as components rather than indicators of a crisis or of aggressive financial  management. The purpose of this study is to contribute to the knowledge of financial  restructuring, company signaling, and market efficiency in emerging countries. The  dissemination of data extracted from the expanding Saudi capital market is how this  objective is fulfilled. These results shed light on the need of conducting an evaluation  of activities that are targeted at decreasing capital within the context of a strategic  governance framework that is in accordance with the goals of Saudi Arabia's Vision  2030. As a result of this, they bring attention to the possible importance that these  activities may have in increasing the confidence of investors and assuring the  organization's capacity to continue operating financially in the future.
Keywords: Capital Reduction Announcement; Abnormal Returns; Event Study; Saudi Stock Exchange